Adjuvant Pertuzumab and Trastuzumab in Early Human Epidermal Growth Factor Receptor 2-Positive Breast Cancer in the APHINITY Trial: Third Interim Overall Survival Analysis With Efficacy Update - Loibl, S (2024)
Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported. The APHINITY trial (ClinicalTrials.gov identifier: NCT01358877) previously demonstrated that pertuzumab added to adjuvant trastuzumab and chemotherapy improved invasive disease-free survival (iDFS) for patients with early human epidermal growth factor receptor 2-positive (HER2+) breast cancer (BC). Here, we report the preplanned third interim analysis of overall survival (OS) and a descriptive updated iDFS analysis with 8.4 years of median follow-up of 4,804 patients in the intent-to-treat population. The 8-year OS was 92.7% in the pertuzumab versus 92.0% in the placebo group (hazard ratio [HR], 0.83 [95% CI, 0.68 to 1.02]; P =.078, above the 0.006 significance threshold). The HR was 0.80 [95% CI 0.63 to 1.00] in the node-positive cohort and 0.99 [95% CI, 0.64 to 1.55] in the node-negative cohort. Updated results of 8-year iDFS in the node-positive cohort showed an absolute improvement of 4.9% favoring pertuzumab (86.1% v 81.2%; HR, 0.72 [95% CI, 0.60 to 0.87]). The node-negative cohort did well without adding pertuzumab (8-year iDFS and OS in the placebo group were 93.3% and 96.4%, respectively). The iDFS benefit was seen in the hormone receptor-negative (HR, 0.82 [95% CI, 0.64 to 1.06]) and HR+ cohorts (HR of 0.75 [95% CI, 0.61 to 0.92]). Despite improvement in overall iDFS, the addition of pertuzumab did not improve OS at this third interim analysis.